Preliminary study on the length - weight relationship and enumeration of coliforms by moist heat of "kulot oysters (C. Palmipes). - Oberes, Cynthia B. (College of Fisheries, University of the Philippines, 1979)
The experiment was conducted in two phases. The first phase dealt with the oyster meat yield and length-weight correlation of C. Palmipes (kulot) ranging in length from 2 to 6 centimetres and with weights ranging from 4.5 to27.6 grams. The samples were taken at the Binakayan oyster farm, bureau of fisherier and aquatic resources, Binakayan, Cavite. Based on these studies, the percentage most yield is not correlated with regards to the volume (cm3) and whole weight of the oyster. The correlation coefficient (r) for all the statistical parmeters (percent meat, versus whole weight. Volume, maximum length, average height of the oyster shell) is almost near to zerp, which indicates a weak or vary sight correlation. The b values (of the length-weight equations log W= Log a +bLog L) using average length were computed to be 2.005, while using maximum height was computed to be 2.20. These indicate that the oyster became more slender as they increased in length. The second phase dealt with the microbiological study and subsequent evaluation on these samples whose coliform count showed negative growth. Based on the results, steaming of oyster at 100 Degree C for 5 minutes is the best among the time-temperature combinations studied wherein the oyster is free from coliforms at the same time the final eating quality is not adversely affected.